Hip decompression combined with bone marrow concentrate and platelet-rich plasma for corticosteroid-induced osteonecrosis of the femoral head: mid-term update from a prospective study. (5th November 2021) - Houdek, Matthew T.; Wyles, Cody C.; Smith, John-Rudolph H.; Terzic, Andre; Behfar, Atta; Sierra, Rafael J.
Abstract : Aims: Bone marrow-derived mesenchymal stem cells obtained from bone marrow aspirate concentrate (BMAC) with platelet-rich plasma (PRP), has been used as an adjuvant to hip decompression. Early results have shown promise for hip preservation in patients with osteonecrosis (ON) of the femoral head. The purpose of the current study is to examine the mid-term outcome of this treatment in patients with precollapse corticosteroid-induced ON of the femoral head. Methods: In all, 22 patients (35 hips; 11 males and 11 females) with precollapse corticosteroid-induced ON of the femoral head underwent hip decompression combined with BMAC and PRP. Mean age and BMI were 43 years (SD 12) and 31 kg/m² (SD 6), respectively, at the time of surgery. Survivorship free from femoral head collapse and total hip arthroplasty (THA) and risk factors for progression were evaluated at minimum five-years of clinical follow-up with a mean follow-up of seven years (5 to 8). Results: Survivorship free from femoral head collapse and THA for any reason was 84% and 67% at seven years postoperatively, respectively. Risk factors for conversion to THA included a high preoperative modified Kerboul angle (grade 3 or 4) based on preoperative MRI (hazard ratio (HR) 3.96; p = 0.047) and corticosteroid use at the time of decompression (HR 4.15; p = 0.039). The seven-year survivorship for patients with grade 1 or 2 Kerboul angles for conversion to THA for articular collapse, and THA for any reason, were 96% and 72%, respectively, versus THA for articular collapse and THA for any reason in patients with grade 3 or 4 Kerboul angles of 40% (p = 0.003) and 40% (p = 0.032). Conclusion: At seven years, hip decompression augmented with BMAC and PRP provided a 67% survivorship free from THA in patients with corticosteroid-induced ON. Ideal candidates for this procedure are patients with low preoperative Kerboul angles and can stop corticosteroid treatment prior to decompression. Cite this article: Bone Jt Open 2021;2(11):926–931.